2017
DOI: 10.1002/prp2.370
|View full text |Cite
|
Sign up to set email alerts
|

Cenerimod, a novel selective S1P1 receptor modulator with unique signaling properties

Abstract: Sphingosine‐1‐phosphate receptor 1 (S1P1) modulators sequester circulating lymphocytes within lymph nodes, thereby preventing potentially pathogenic autoimmune cells from exiting into the blood stream and reaching inflamed tissues. S1P1 receptor modulation may thus offer potential to treat various autoimmune diseases. The first nonselective S1P1‐5 receptor modulator FTY720/fingolimod/Gilenya® has successfully demonstrated clinical efficacy in relapsing forms of multiple sclerosis. However, cardiovascular, hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
(81 reference statements)
1
20
0
Order By: Relevance
“…Cenerimod (ACT‐334441 [molecular weight: 453.5 g/mol]) is a potent, orally active, selective modulator of the sphingosine‐1‐phosphate 1 (S1P 1 ) receptor . S1P 1 receptor modulators reduce the tissue availability of lymphocytes by blocking the egress of lymphocytes from lymphoid organs and are developed for the treatment of autoimmune disorders .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cenerimod (ACT‐334441 [molecular weight: 453.5 g/mol]) is a potent, orally active, selective modulator of the sphingosine‐1‐phosphate 1 (S1P 1 ) receptor . S1P 1 receptor modulators reduce the tissue availability of lymphocytes by blocking the egress of lymphocytes from lymphoid organs and are developed for the treatment of autoimmune disorders .…”
Section: Introductionmentioning
confidence: 99%
“…1 S1P 1 receptor modulators reduce the tissue availability of lymphocytes by blocking the egress of lymphocytes from lymphoid organs 2 and are developed for the treatment of autoimmune disorders. 3 To date, 2 S1P (1) receptor modulators have been granted marketing authorization for the treatment of multiple sclerosis. 4,5 Cenerimod is under clinical development for the treatment of systemic lupus erythematosus (SLE), a complex autoimmune disorder of chronic nature 6,7 that involves autoreactive T and B lymphocytes causing inflammation and tissue damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cenerimod is a potent, orally active, selective S1P 1 receptor modulator with unique signalling properties 19. In the non-clinical setting, cenerimod did not induce bronchoconstriction or vasoconstriction, which are known adverse effects of S1P receptor modulators 19.…”
Section: Introductionmentioning
confidence: 99%
“…Cenerimod is a potent, orally active, selective S1P 1 receptor modulator with unique signalling properties 19. In the non-clinical setting, cenerimod did not induce bronchoconstriction or vasoconstriction, which are known adverse effects of S1P receptor modulators 19. A phase I study in healthy participants showed that cenerimod was well tolerated with no significant safety concerns across a range of doses from 0.5 to 4 mg once daily 20.…”
Section: Introductionmentioning
confidence: 99%